ANALISIS PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) PADA PROSES PEMBELAJARAN KURIKULUM MERDEKA DI SEKOLAH DASAR - Roisatul, Falistya; Dian Fitri Nur Aini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Kurikulum Merdeka is a curriculum with diverse intracurricular learning, with optimal implementation, students have enough time to deepen concepts and strengthen competencies. In implementation, teachers have the freedom to choose various teaching tools by paying attention to students' needs. The process of teaching and learning activities is no longer focused in the classroom, but activities can be carried out anywhere. There are internal and external influences that can cause differences in students' abilities. Students' abilities do not match learning outcomes due to inappropriate levels. Efforts to overcome student levels that do not match the expected achievements include implementing the Teaching at The Right Level approach. This research model is qualitative research. The research model used in this research is a descriptive model that describes the application of the Teaching at The Right Level (TaRL) approach to elementary school independent curriculum learning. Research location in Malang City elementary school. The subjects in this research were elementary school teachers in Malang City. The instruments used in this research were interview guidelines, observation guidelines, questionnaires and documentation.